The fix : how countries use crises to solve the world's worst problems - Tepperman, Jonathan (Tim Duggan Books, 2016)
"Identifies 10 pervasive and seemingly impossible challenges including immigration reform, income inequality, political corruption and Islamic terrorism and shows that each has a solution, and not merely a hypothetical one, but one that has been proven in a real hotspot in the world, "--NoveList